Phoenixin 14 ameloriates pancreatic injury in streptozotocin-induced diabetic rats by alleviating oxidative burden - ÖZDEMİR KUMRAL, ZARİFE NİGAR; YÜKSEL, MERAL; AKAKIN, DİLEK; ERZİK, CAN; HAKLAR, GONCAGÜL (My University, 2022)
Phoenixin-14 (PNX) is a neuropeptide that has been shown to prevent oxidative damage and stimulates insulin secretion. We investigated the effects of PNX on pancreatic injury induced by streptozotocin (STZ), and nicotinamide (NAD). Male Sprague-Dawley rats, in control (C) and diabetic (STZ) groups, were treated with either saline, or PNX (0.45 nmol/kg, or 45 nmol/kg) daily for 3 days 1 week after STZ injection. Fasting blood glucose (FBG) and gastric emptying rate (GER) were measured. Tissue and blood samples were collected. PNX treatments prevented pancreatic damage and beta cell loss. Increased luminol and lucigenin levels in the pancreas, ileum and liver tissues of STZ groups were alleviated by PNX treatment in pancreatic and ileal tissues. PNX0.45 decreased FBG without any change in insulin blood level and pancreatic mRNA. GER increased in all diabetic rats while PNX0.45 delayed GER only in the C group. PNX diminishes pancreatic damage and lowers FBG by reducing oxidative load.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; inflammation; insulin; gastric emptying; glucose; free radicals; MPO; ORAL GLUCOSE-TOLERANCE; PEPTIDE; TESTOSTERONE; MODULATION; NESFATIN-1; EXPRESSION; SECRETION; STRESS; DAMAGE; SITES; inflammation; insulin; gastric emptying; glucose; free radicals; MPO